Theoretical risk of genetic reassortment should not impede development of live, attenuated Rift Valley fever (RVF) vaccines commentary on the draft WHO RVF Target Product Profile. (7th August 2020) - Monath, Thomas P.; Kortekaas, Jeroen; Watts, Douglas M.; Christofferson, Rebecca C.; Desiree LaBeaud, Angelle; Gowen, Brian B; Peters, Clarence J.; Smith, Darci R.; Swanepoel, Robert; Morrill, John C.; Ksiazek, Thomas G.; Pittman, Phillip R; et al.
Highlights: The World Health Organization has published draft Target Product Profiles (TPPs) for veterinary and human vaccines against Rift Valley Fever virus (RVFV) The draft TPPs contain restrictive requirements for live attenuated vaccines aimed at reducing the risk of genetic reassortment of live vaccines with wild-type RVFV and related bunyaviruses. This review assesses the risk of genetic reassortment, and concludes that there is no evidence that such events have occurred despite a long history of use of live RVFV vaccines, and that if reassortment occurred it would be of no consequence. The hypothetical risks of reassortment do not outweigh the benefits of vaccination and should not impede acceptance of multiple promising new vaccines in development. Abstract: In November 2019, The World Health Organization (WHO) issued a draft set of Target Product Profiles (TPPs) describing optimal and minimally acceptable targets for vaccines against Rift Valley fever (RVF), a Phlebovirus with a three segmented genome, in both humans and ruminants. The TPPs contained rigid requirements to protect against genomic reassortment of live, attenuated vaccines (LAVs) with wild-type RVF virus (RVFV), which place undue constraints on development and regulatory approval of LAVs. We review the current LAVs in use and in development, and conclude that there is no evidence that reassortment between LAVs and wild-type RVFV has occurred during field use, that such a reassortment event if it occurred would have no untoward consequence, and that the TPPs should be revised to provide a more balanced assessment of the benefits versus the theoretical risks of reassortment.